Pre-vaccination Schistosoma mansoni and hookworm infections are associated with altered vaccine immune responses: a longitudinal analysis among adolescents living in helminth-endemic islands of Lake Victoria, Uganda - Natukunda, Agnes; Zirimenya, Ludoviko; Nkurunungi, Gyaviira; Nassuuna, Jacent; Nkangi, Ronald; Mutebe, Alex; Corstjens, Paul L. A. M.; van Dam, Govert J.; Elliott, Alison M.; Webb, Emily L. (Frontiers in Immunology, 2024)
Background: Variations in vaccine responses have been observed between populations. A role for helminth infections has been proposed due to their immunomodulatory properties. In a secondary analysis of data from a randomised trial assessing effects of anthelminthic treatment on vaccine responses, we examined associations between helminth infections at baseline prior to vaccine administration, and vaccine responses among adolescents (9-17 years) in Koome Islands, Lake Victoria, Uganda.: Participants received BCG [week 0], yellow fever (YF-17D), oral typhoid (Ty21a), HPV-prime [week 4], and HPV-boost, tetanus/diphtheria [week 28]. Outcomes were BCG-specific interferon-ɣ ELISpot responses and antibody responses to yellow-fever-, typhoid-, HPV-, tetanus-and diphtheriaspecific antigens measured at two time points post vaccination. S. mansoni infection was determined as positive if either the plasma Circulating Anodic Antigen (CAA) assay or stool PCR were positive. Hookworm and Strongyloides were determined by stool PCR. Linear mixed effects regression was used to assess associations.Results: Among 478 adolescents, 70% were Schistosoma mansoni (Sm) infected and 23% hookworm infected at baseline. Sm was associated with lower Salmonella Typhi O:LPS-specific IgG responses (adjusted geometric mean ratio (aGMR) 0.69 (0.57-0.83)), and hookworm with higher diphtheriaspecific IgG (aGMR 1.16 (1.02, 1.31)) and lower HPV-16-specific IgG (aGMR 0.70 (0.55, 0.90)) postvaccination. High Sm intensity was associated with lower BCG-specific interferon-g and S. Typhi O:LPSspecific IgG.We found inverse associations between Sm and responses to two live vaccines, whereas hookworm was positively associated with diphtheria-specific IgG. These findings support the hypothesis that helminth infections can modulate vaccine responses, while also highlighting potential heterogeneity in the direction of these effects.